The lion's game : a novel - DeMille, Nelson (New York : Warner Books, 2000)
Detective John Corey of Plum Island fame returns to take on one of the most incredible serial killers of all time--a young Arab, known as "The Lion" who will stop at nothing in his quest for revenge against the Americans who bombed Libya and killed his family.
Keywords: Corey, John (Fictitious character) -- Fiction; Terrorism -- Prevention -- Fiction; Serial murders -- Fiction; Libya -- History -- Bombardment, 1986 -- Fiction; Adventure stories